Model‐based meta‐analysis of salbutamol pharmacokinetics and practical implications for doping control. (22nd March 2022) - Courlet, Perrine; Buclin, Thierry; Biollaz, Jérôme; Mazzoni, Irene; Rabin, Olivier; Guidi, Monia
Abstract: Salbutamol was included in the prohibited list of the World Anti‐Doping Agency (WADA) in 2004. Although systemic intake is banned, inhalation for asthma is permitted but with dosage restrictions. The WADA established a urinary concentration threshold to distinguish accordingly prohibited systemic self‐administration from therapeutic prescription by inhalation. This study aimed at evaluating the ability of the WADA threshold to differentiate salbutamol therapeutic use from violation of antidoping rules. Concentration‐time profile of salbutamol in plasma and its excretion in urine was characterized through a model‐based meta‐analysis of individual and aggregate data collected after administration of a large range of doses following different modes of administration and under a variety of conditions. The developed model adequately fitted salbutamol plasma and urine concentration‐time profiles of the 13 selected studies. Model‐based simulations confirmed that a wide range of salbutamol urine concentrations might be measured after drug intake. Although violation of the WADA Code can be strongly suspected in individuals showing very high salbutamol urine concentrations, uncertainty remains for values close to the WADA threshold as they can be compatible with both permitted therapeutic use and violation. Although not entirely discriminant, the current WADA rule is globally supported by our appraisal. It could be further improved by a slight and reasonable adjustment of inhaled daily dosages allowed for therapeutic use. Our model might help antidoping experts in the evaluation of suspected doping cases through confronting the athlete's urine measurements with their allegations about salbutamol treatment.